EFEKTIVITAS PEMBELAJARAN FISIKA DENGAN PENERAPAN PENDEKATAN CTL TERHADAP KETERAMPILAN PROSES IPA DAN PSIKOMOTOR SISWA KELAS VI SDN 011 KERUMUTAN (Jurnal Pilar Sains, 2008)
The purpose of this research is to know the effectiveness of physic learning through contextual teaching andlearning approach in the result of student science process skill and psychomotor skill achievement. Thesubject of this research is 30 students of SDN 011 Kerumutan in period 2007/2008. The chosen of mainsubject is Heat Transfer. Data is collected by giving the piper and pencil test and the applicative psychomotortest after finishing the subject. The data of this result is analyzed descriptively with consists of: student’sachievement and learning completeness. The result analysis to the science process skill showed the student’sachievement is categorized good, material completeness is categorized not complete and learningcompleteness is categorized complete. The result analysis to the psychomotor skill showed the student’sachievement is categorized good, material and learning completeness is categorized not complete. So, physiclearning by using contextual teaching and learning approach is clarified effectiveless for science processskill and psychomotor skill achievement of sixth year students at SDN 011 Kerumutan, Pelalawan district.Key words: contextual teaching and learning, psychomotor skill, science process skill